PRINSIP KERJA SAMA PERCAKAPAN DI KANTOR IMIGRASI KELAS 1 BENGKULU - Putri Juliastuti; Suryadi Suryadi; Ngudining Rahayu (Jurnal Korpus, 2018)
This research aims to describe the forms of compliance and violation of cooperation principle which have been occurred at Class 1 of Bengkulu Immigration Office. This research is a qualitative descriptive research. Sources of data in this research were officers and applicants. This research data was a speech event that it told by officers and applicants which contain of  cooperation principle in it. Data collection was conducted start from date March 20th until April 6th, 2017. The instrument used in this research were a human instrument with hardware tools in the form of notebooks and smartphones, and software such as limitation and understanding maxims of conversation/cooperation principle (maxim quantity, maxim quality, maxim relevance, and maxim manner. Data collected by recording technique and note technique. Data analysis were done by steps as follow;  data transcription, data identification, data classification, data interpretation, data validation, and data conclusion. The results of this research showed that two conclusions. First, the forms of compliance with the cooperation principle which have been occurred at center of Class 1 of Bengkulu Immigration Service which consist from four maxims based on Grice maxim and six maxims of mixed results between the maxim of quantity, quality, relevance, and manner were found when conducting research in the field. Second is the forms of violation of cooperation principle at center of Class 1 of Bengkulu Immigration Service which consist from four maxims based on Grice maxim and five maxims mixed found when conducting research in the field. Keywords: Cooperation Principle, Conversation, Maxim